Evidence of Cu(I)/Cu(II) Redox Process by X-ray Absorption and EPR Spectroscopy: Direct Synthesis of Dihydrofurans from β-Ketocarbonyl Derivatives and Olefins - Yi, Hong; Liao, Zhixiong; Zhang, Guanghui; Zhang, Guoting; Fan, Chao; Zhang, Xu; Bunel, Emilio E; Pao, Chih-Wen; Lee, Jyh-Fu; Lei, Aiwen (Chemistry : a European journal, 2015)
The Cu(I)/Cu(II) and Cu(I)/Cu(III) catalytic cycles have been subject to intense debate in the field of copper-catalyzed oxidative coupling reactions. A mechanistic study on the Cu(I)/Cu(II) redox process, by X-ray absorption (XAS) and electron paramagnetic resonance (EPR) spectroscopies, has elucidated the reduction mechanism of Cu(II) to Cu(I) by 1,3-diketone and detailed investigation revealed that the halide ion is important for the reduction process. The oxidative nature of the thereby-formed Cu(I) has also been studied by XAS and EPR spectroscopy. This mechanistic information is applicable to the copper-catalyzed oxidative cyclization of β-ketocarbonyl derivatives to dihydrofurans. This protocol provides an ideal route to highly substituted dihydrofuran rings from easily available 1,3-dicarbonyls and olefins.